Perfect Day At Work : Professional Agency Between External And Internal Factors In ECEC - Ruuska, Vilma (2024)
Early Childhood Education and Care (ECEC) in Finland has faced organizational change in 2013 that has affected the aims, objectives and implementation of ECEC services. The field of ECEC is a mix of official regulations and obligations and the professional’s strong sense of agency and autonomy regarding their work. The field has had long lasting challenges with having enough qualified professionals. Additionally, the poor organization of the work and insufficient recourses have been the reason for low job-engagement for professionals in ECEC. In this research the aim is to investigate how professionals in the field of early childhood education would prefer to work with the changed aims and obligations of the domain. The narrative research method was used to collect stories from professionals working in daycare. ECEC teachers, social pedagogues and caretakers were asked to tell a short story about their perfect day at work. Stories were analyzed using thematic analysis method. The results show that ECEC professionals would prefer to have time to focus on the pedagogy and the children. This often requires support from colleagues, manager or official level to have time to use their agency in a meaningful way. They would also prefer to have better work-life balance and have influence on their working times. Results also highlight how intervened the internal and external structures of the work are which challenges the professional agency. Keywords: Early Childhood Education and Care, Professional Agency, Educational Development, Work Structures